Teacher Competency in Implementing Learning Based on Scientific Approach in SMPN 1 & 2 Kendari - Tri Maniarta Sari; Ernawati Ernawati; Asmawati Munir; Parakkasi - (Journal of Biological Science and Education, 2020)
Curriculum 2013 teachers are required to perform a scientific study. So it's essential to see how the competence of teachers in learning based on a scientific approach. Based on this study aims to describe (1) the ability of science teachers in designing learning based on the scientific approach in SMPN 1 and SMPN 2 Kendari (2) the competence of science teachers in implementing the learning-based approach is scientifically appropriate curriculum, 2013 in SMPN 1 and SMPN 2 Kendari. The collection of data is done (This sentence appears to be written in the passive voice. Consider writing in the active voice) using an instrument study lesson plans, teaching observation, and interviews. The sampling using a purposive sampling method or sample aims. Samples are 13 teacher teaching science classes VII and VIII derived from two schools SMPN 1 and SMPN 2 Kendari. The results showed that (1) the competence of science teachers in designing learning based on appropriate scientific approach was in functional categories, (2) the ability of science teachers in implementing the learning based on proper scientific approach was good enough grade.